Legal Protection Of Children From Victims Of Criminal Acts With The Mode Of Romantic Relationship By Adults - Tiara Rebecca Kezia Siregar; Beniharmoni Harefa (UNIVERSITAS PAKUAN, 2026)
This study examines the legal protection for children as victims of criminal acts involving the